Profitability Analysis For Measurement Of Financial Performance Of Mitra Perdana Sidoarjo Cooperative - Siti Khasanaturrohmah; Totok Mardianto (JURASIMA, 2024)
This study aims to analyse the financial performance of Koperasi Mitra Perdana Sidoarjo from a profitability perspective using the Net Profit Margin, Benefit to Asset, and Benefit to Capital ratios in 2020-2022. This research uses a qualitative descriptive method, using cooperative financial statement data. Data analysis was carried out by calculating the profitability ratio according to the formula and based on the Minister of KUKM Regulation Number 06/Per/M.KUKM/V/2006. The results showed: 1) Net Profit Margin Ratio in unhealthy condition during 2020-2022, 2) Benefit Over Assets Ratio is in healthy condition, 3) Benefits Over Capital Ratio is in healthy condition. The findings indicate that cooperative management needs to improve net profit margins. The research suggests efforts to improve financial performance, especially in the aspect of net profit margin which still requires development.